2013
DOI: 10.1177/0004867413500350
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deconstruction of parenting in schizophrenia: The role of theory of mind

Abstract: Second-order theory of mind deficits are specifically associated with parental role dysfunction of patients with schizophrenia. Novel treatment strategies targeting theory of mind may improve parenting abilities in individuals with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…In a study investigating the association between functional ability in the parental role (i.e., active involvement and affective relationship) and cognitive performance, and level of insight and motivation, individuals with schizophrenia who were parents underwent comprehensive assessments for neurocognition, social cognition (ToM, emotion processing, social perception, and attributional bias), motivation and insight, and social functioning (using the Groningen Social Disabilities Schedule) [ 78 ]. The results demonstrated that deficits in first- and second-order ToM were significantly associated with parental role dysfunction, as were cognitive flexibility, speed of processing, and motivation [ 78 ]. Second-order ToM was found to be a specific predictor of parental role on logistic regression analysis [ 78 ].…”
Section: Core Domains Of Social Cognition In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…In a study investigating the association between functional ability in the parental role (i.e., active involvement and affective relationship) and cognitive performance, and level of insight and motivation, individuals with schizophrenia who were parents underwent comprehensive assessments for neurocognition, social cognition (ToM, emotion processing, social perception, and attributional bias), motivation and insight, and social functioning (using the Groningen Social Disabilities Schedule) [ 78 ]. The results demonstrated that deficits in first- and second-order ToM were significantly associated with parental role dysfunction, as were cognitive flexibility, speed of processing, and motivation [ 78 ]. Second-order ToM was found to be a specific predictor of parental role on logistic regression analysis [ 78 ].…”
Section: Core Domains Of Social Cognition In Schizophreniamentioning
confidence: 99%
“…The results demonstrated that deficits in first- and second-order ToM were significantly associated with parental role dysfunction, as were cognitive flexibility, speed of processing, and motivation [ 78 ]. Second-order ToM was found to be a specific predictor of parental role on logistic regression analysis [ 78 ].…”
Section: Core Domains Of Social Cognition In Schizophreniamentioning
confidence: 99%
“…[168][169][170][171] Such subtle social and cognitive deficits from schizophrenia possibly affect parental sensitivity more so than other illness features. 172 Reduced parenting capacity may lead parents to be less responsive, sensitive or energetic, remote, intrusive, or overprotective with their child. 4,36,152,159,167,[173][174][175][176] Importantly, adoptees at FHR for schizophrenia spectrum disorder, when exposed to parental communication deviance of adoptive parents were more likely to show psychiatric disorders, including schizophrenia spectrum disorders.…”
Section: Postpartum and Childhood Environmental Risks And Mechanismsmentioning
confidence: 99%
“…More recently, Mehta et al (2014) studied the relationship between various indices of social cognition, including ToM, and ‘parenting role function’ (i.e. the extent to which a parent is involved in his or her child's life, and the quality of the parent–child relationship) in a sample of parents with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%